Efforts to Control Organic Solvent Hazards in the Informal Sector Industry - Ana Islamiyah Syamila; Evi Riski Permatasari; Ainul Qismatil Katsiiroh; Muhammad Arizal Aulia; Arta Raya Nurvita; Reny Indrayani (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
One of the hazards in the workplace that can cause occupational diseases is chemicals such as organic solvents. Organic solvents consist of various types of organic substances which are all toxic. Considering this, there is a need for intervention activities for the industrial world, especially the informal sector. This intervention is manifested in a community service program at the Putra Jaya Las Bengkel in Jember Regency. The purpose of this activity is to administratively control the dangers of organic solvents. The method used is counseling and direct practice with the media of pocket books, posters, chemical labels and material safety data sheets (MSDS). The results of the pretest and post-test evaluations showed an increase in knowledge about the dangers and control of organic solvents among workers by 12.5% from an average of 80 to 90. In addition, administrative practices for controlling organic solvents have been carried out in the form of posters, label repairs on organic solvent containers, and provision of MSDS. Overall, it is concluded that this community service activity has effectively increased workers' knowledge about the dangers and control of organic solvents, and has succeeded in increasing the safety of using organic solvents in the workplace. It is recommended that further activities be carried out to maintain the commitment and consistency of the target audience in implementing organic solvent hazard control.